Musical staff - Kelly, Brendan; Kesselring, Kara; Richelieu, Rochelle; Hercules, Bob; Wavelength Inc. (Chicago, IL : Wavelength Inc., 2004)
Features parodies of popular musical songs focused on today's most pressing educational issues
Another school year, another show! -- Testing for whose school's on top -- Mentor -- All I want is a room somewhere -- On the street where we want to live -- You should have crammed all night -- Don't cry to me whiney students -- I feel stupid -- Maria -- America! -- Teachers -- Hello Dubya! -- School vouchers are all right -- Politicians! -- If I just had tenure -- How do you solve a problem like Maria? -- Sit down you're rockin' the Board -- I got support right here! -- Greased luncheon -- Summer's comin' -- Teach on down the road
Title from title screen
Executive producer, Jim Winter ; editor, Todd Wood ; choreography, Brad Harbaugh
Brendan Kelly, Anne Sheridan Smith & Kara Kesselring
DVD format
Keywords: Teaching -- Humor; Wit and humor in education; Wit and humor, Musical; Parody (Music)